Funkcjonowanie samorządów pracowniczych w wybranych krajach realnego socjalizmu - Wdzięczak, Janusz (Annales. Etyka w Życiu Gospodarczym, 2016)
The aim of the article is to present the attempts of establishing institutions of a system of worker’s self-management in the selected countries of the so-called real socialism system in Eastern Europe. The analysis considers three of those countries, namely Yugoslavia, Poland and Hungary, whose experiences in participation of the employees’ implementation were the most significant. Particular attention was paid to the evolution of socialist regimes approach to workers’ self-management. The paper tries to answer the question whether workers’ self-management posed a threat to the socialist regimes persistence. The research method used in the study is an indepth survey and analysis of literature and legal acts.